Review: Ecological impact and bioactive profile of the invasive species Solanum elaeagnifolium in the Gaza Strip, Palestine - MOHAMAD ABOU AUDA; MOHAMMED ELEYAN (Society for Indonesian Biodiversity, 2025)
Abstract. Abou Auda M, Eleyan M. 2025. Review: Ecological impact and bioactive profile of the invasive species Solanum elaeagnifolium in the Gaza Strip, Palestine. Biodiversitas 26: 3485-3513. Solanum elaeagnifolium (Silverleaf nightshade) is an aggressive invasive species in the Middle East, particularly in the Gaza Strip, Palestine, where it poses significant ecological and agricultural threats. This review provides a comprehensive analysis of the botany, ecology, phytochemistry, pharmacology, and toxicology of S. elaeagnifolium in the Gaza Strip. It is the first study to focus on its invasive potential and bioactivity in this region, with an emphasis on the need for monitoring and effective control strategies. A comprehensive literature review was conducted, sourcing data from PubMed, Scopus, Web of Science, and Google Scholar databases up to April 2025. The plant contains flavonoids, glycoalkaloids, phenolic acids, and saponins. Nutritional content includes crude fiber (28-32% in leaves; 27-32% in flowers), protein (13-14%), potassium (2.6% in leaves; 3.3% in flowers), and phosphorus (0.21-0.24%). Toxicological studies reported hepatotoxic effects at 2000 mg/kg fruit extract (p<0.001), elevated ALT/AST and creatinine (p<0.01), and altered RBC counts. Antioxidant activity showed DPPH IC?? of 0.025 mg/mL (seeds) and 35.15 µg/mL (fruit). Enzyme inhibition assays revealed lipase IC?? of 0.167 mg/mL (leaves) and 0.106 mg/mL (fruit), and antiglycation IC??: 3.997 mg/mL. Antimicrobial assays showed broad-spectrum activity, with inhibition zones ranging from 12-20 mm and MIC values of 1.25-2.5 mg/mL against multiple gram-positive and gram-negative bacteria. Ecologically, S. elaeagnifolium develops an extensive root system and vigorous rhizome spread, which significantly enhance its invasiveness. Solanum elaeagnifolium presents a significant ecological threat in the Gaza Strip, with its invasive behavior driven by its deep root system and vigorous rhizome spread. Preliminary phytochemical screening indicates the presence of alkaloids and saponins, warranting further in vitro validation. The plant’s bioactive properties, such as its antimicrobial and antioxidant activities, suggest its potential for pharmacological applications. However, further experimental studies are needed to assess the clinical viability and toxicity of these compounds.